Komentarz do bibliografii przekładów literatury czeskiej w Polsce i literatury polskiej w Czechach w 2015 roku - Mroczek, Izabela (Przekłady Literatur Słowiańskich, 2016)
A commentary on the Bibliography of translations of Czech literature in Poland and Polish literature in the Czech Republic in 2015 Annotations to the bibliography of literary translations of Czech literature in Poland and Polish literature in the Czech Republic in 2015 is a summation of events in both the Polish and Czech publishing markets, connected with the publishing of literary translations of Czech literature in Poland and Polish literature in the Czech Republic in 2015. Within the framework of annotation, the most important literary translations in this language pair were presented, pointing to the leading publishers and active translators. An evaluative review is linked to a compact outline of the development of Polish and Czech publishers that handle Polish literature in the Czech Republic and Czech literature in Poland. Key words: translations of Czech literature in Poland, translations of Polish literature in the Czech Republic, translators of Czech literature in Poland, translators of Polish literature in the Czech Republic